Autoamputation of an ovarian mature cystic teratoma: a case report and a review of the literature - Lee, Keun Ho (World J Surg Oncol, 2016)
BACKGROUND: Torsion is known to be the most frequent complication of ovarian teratomas. Torsion of the adnexa usually manifests with severe abdominal pain and is treated as an acute surgical emergency. However, it may be asymptomatic. Autoamputation of an ovary, along with other adnexal structures, due to previous torsion is extremely rare. CASE PRESENTATION: A parasitic ovarian teratoma that underwent torsion, autoamputation, and reimplantation was found incidentally during laparoendoscopic single-site surgery (LESS). The amputated tumor was located in the omentum of the right upper abdomen of a patient with concomitant torsion of a left ovarian teratoma. The right ovary and tube were absent even though she had no surgical history. This finding could be interpreted as an autoamputation of the adnexa due to torsion of a previous ovarian cyst arising from the right ovary. We removed all masses by LESS. CONCLUSIONS: Although both ultrasonography and computed tomography were performed preoperatively in our patient, the correct diagnosis of autoamputation and exact localization of the teratoma were extremely difficult. Physicians should consider the possibility of an autoamputated ovarian cyst even if preoperative radiography shows no calcification.